CFST arch bridge seismic response analysis considering near-fault ground motion pulse characteristics. Issue 1 (September 2020) - Fan, Xing; Xiaofeng, Li
Abstract: Based on a long-span CFST arch bridge finite element model, nonlinear time-history response analysis is carried out. It is found that the key section of the connection of arch rib and bridge deck is a particular location with larger seismic response. The fling-step type TCU068-E is more liable to excite a greater seismic response at arch rib sections. Through seismic wave dyadic wavelet analysis, the wavelet component in the structure fundamental frequency band is reconstructed to be a new seismic excitation. The results indicate that the low-frequency component of TCU068-E is strong, and larger structural seismic response is generated accordingly.